2019
DOI: 10.1002/jmv.25510
|View full text |Cite
|
Sign up to set email alerts
|

High rate of occult hepatitis B virus infection in hemodialysis units of KwaZulu‐Natal, South Africa

Abstract: Occult hepatitis B virus (HBV) infection (OBI) is defined as the presence of HBV DNA in the liver with or without detectable HBV DNA in the serum of individuals testing HBV surface antigen (HBsAg) negative using currently available assays. The prevalence of OBI among patients receiving hemodialysis (HD) treatment remains poorly characterized in South Africa despite the high prevalence of HBV. We sought to determine the prevalence of OBI in HD units in tertiary hospitals of KwaZulu‐Natal and to characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…in their study, PLHIV were on treatment for HBV [29] Similarly, a study by Dzudzor et. al., among chronic kidney patients on hemodialysis in Ghana in 2024 who were HBeAg negative but HBcAb positive, found 7.3% had detectable HBV DNA [30] The OBI prevalence found in this study was relatively lower compared to a study in South Africa (19.1%) [31][32][33], and significantly lower than another study among PLHIV in Morocco (68.4%) [34]. Nonetheless, a relatively lower prevalence has been reported elsewhere.…”
Section: Plos Onecontrasting
confidence: 66%
“…in their study, PLHIV were on treatment for HBV [29] Similarly, a study by Dzudzor et. al., among chronic kidney patients on hemodialysis in Ghana in 2024 who were HBeAg negative but HBcAb positive, found 7.3% had detectable HBV DNA [30] The OBI prevalence found in this study was relatively lower compared to a study in South Africa (19.1%) [31][32][33], and significantly lower than another study among PLHIV in Morocco (68.4%) [34]. Nonetheless, a relatively lower prevalence has been reported elsewhere.…”
Section: Plos Onecontrasting
confidence: 66%
“…Overall, our literature review shows that it is currently challenging to estimate the exact prevalence of OBI, mainly due to the scarcity of studies in healthy populations and the lack of a standard diagnostic test. The reported prevalence varies widely from <1% to >50%, with higher rates found in Africa and Asia (Msomi et al, 2019;Ye, 2019) (Figure 1). Only one study has been published recently in Oceania and North America, showing that further epidemiological investigations in these areas would be important.…”
Section: )mentioning
confidence: 99%
“…Substitutions V190 and F134I in genotype A samples have been reported in some studies, however their contribution to occult hepatitis has not yet been described. (18,28) Further studies are needed to determine effects of these and other variation we found in this study on HBsAg and HBV. In particular, T123A escape mutation located in the MHR of the S gene was distinctly present in one patient (sample BSM590).…”
Section: Discussionmentioning
confidence: 91%